2017
DOI: 10.18103/mra.v5i7.1252
|View full text |Cite
|
Sign up to set email alerts
|

Cystatins as regulators of cancer

Abstract: The cystatins, natural inhibitors of cysteine proteases, act as metastasis suppressors for a wide variety of different cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…In this research, cystatin C was significantly low in prostate cancer subjects compared with control. This supports the findings of Cox (2017) and Wang et al, (2018) where cystatin C was reported to be low in prostate cancer. The decreased level may be the reason for cancer progression since cystatin C is believed to play a key role in tumor suppression.…”
Section: Resultssupporting
confidence: 92%
“…In this research, cystatin C was significantly low in prostate cancer subjects compared with control. This supports the findings of Cox (2017) and Wang et al, (2018) where cystatin C was reported to be low in prostate cancer. The decreased level may be the reason for cancer progression since cystatin C is believed to play a key role in tumor suppression.…”
Section: Resultssupporting
confidence: 92%
“…Cysteine proteases, expressed widely in tissues, are a group of intracellular proteins with protein degradation activity which are associated with a wide variety of biological processes, including inflammation, modulation of the immune response and facilitating the progression of malignant tumors (79). Previous clinical studies have revealed that the cystatin superfamily proteins inhibit the proteolytic activity of cysteine proteases specifically in attenuating the aggressiveness of various malignant tumors (1012).…”
Section: Introductionmentioning
confidence: 99%